Neonatal intensive care nurses’ assessment of preterm infants’ pain and sedation: inter-rater reliability of the neonatal pain, agitation, and sedation scale - Albayrak, Selvinaz; Kan Öntürk, Zehra; Şen, Elif; Yayla, Melike (Frontiers in Pediatrics, 2026)
BackgroundTimely and accurate assessment of pain and sedation in newborns is essential for effective management. Therefore, neonatal pain and sedation assessment remains a key global issue in neonatal intensive care unit (NICU) nursing practice. This study examined the inter-rater reliability of Neonatal Pain Agitation, and Sedation Scale (N-PASS) scores among NICU patients.MethodsThis prospective observational study assessed agreement among 19 NICU nurses and two independent researchers who completed 190 observations from 82 preterm infants. Each evaluator rated N-PASS independently and blindly. Agreement among three raters—a nurse and two researchers—were analyzed using the intraclass correlation (ICC) and the Fleiss kappa test.ResultsAgreement levels varied across N-PASS subscales. The ICC and kappa values indicated moderate-to-good reliability for the pain/agitation subscale, whereas the ICC values for the sedation subscale indicated excellent or moderate reliability. Nurses assigned higher mean pain/agitation scores than researchers.ConclusionsNICU nurses must improve their N-PASS assessment skills for both pain and sedation. NICU nurse managers should prioritize improving these competencies to improve pain experiences and ensure adequate sedation, given their significant impact on short- and long-term outcomes in preterm infants.